2019
DOI: 10.1177/1933719118812739
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Immunosuppressive Drugs on Human Placental Explants

Abstract: The use of immunosuppressive drugs guarantees the vitality of the graft and allows gestation in spite of intercurrences such as prematurity and intrauterine growth restriction. However, little is known about the direct effects of immunosuppressive drugs on placental cells. We investigated the effects of immunosuppressive drugs in the chorionic villous explants from human term placentas of healthy gestations. Human placental explants from term gestations (37-39 week gestational age, n = 12) were exposed to cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
(78 reference statements)
0
3
0
3
Order By: Relevance
“…A protective effect on endothelial function has been described, but there was no influence on sFlt-1 and soluble endoglin release (19). In a similar study, azathioprine significantly increased sFlt-1 and PlGF expressions on term placenta explants after 24 hours of incubation when compared to controls (20). However, there are no studies evaluating whether these drugs affect angiogenic and antiangiogenic levels in pregnant women.…”
Section: Discussionmentioning
confidence: 92%
“…A protective effect on endothelial function has been described, but there was no influence on sFlt-1 and soluble endoglin release (19). In a similar study, azathioprine significantly increased sFlt-1 and PlGF expressions on term placenta explants after 24 hours of incubation when compared to controls (20). However, there are no studies evaluating whether these drugs affect angiogenic and antiangiogenic levels in pregnant women.…”
Section: Discussionmentioning
confidence: 92%
“…A large first trimester placenta is associated with macrosomia and large for gestational age 29 . A study performed in term placental explants of healthy gestations has shown that thiopurines perturbs placental homeostasis and more specifically villous metabolism 30 . Further studies are needed to assess whether, and how thiopurines interfere with placental development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the literature to date indicates that the dosage of prednisone should be upregulated during single drug maintenance; more studies are needed to identify the specific dose. Although AZA may be a safe therapy for patients with NMOSD occurring during pregnancy ( 39 ), many patients in our cohort refused to use AZA during pregnancy because of concerns about the adverse effects of this drug. In relation to this, monoclonal antibodies are increasingly used in pregnancy ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%